Smart City and Urban Logistics - Research Trends and Challenges: Systematic Literature Review - Chocholac, Jan; Kucera, Tomas; Sommerauerova, Dana; Hruska, Roman; Machalik, Stanislav; Krupka, Jiri; Hyrslova, Jaroslava (Communications - Scientific Letters of the University of Zilina, 2023)
The paper presents a systematic quantitative and qualitative literature review and classification of the last decades resources for a comprehensive and coherent view of smart city and urban logistics research trends and challenges. The review fully respects a six-step systematic literature review guideline and covers ninety-nine peer-reviewed articles from Web of Science Core Collection database.
Keywords: smart city; logistics; technology; mobility; vehicle routing problem; city logistics